The dynamics of electricity grid operation with increasing renewables and the path toward maximum renewable deployment. (July 2015) - Li, Xuping; Paster, Mark; Stubbins, James
Abstract: This paper presents an overview and analysis of the dynamics and unique impacts of variable renewables on the grid, and identifies the bottleneck problems and solutions associated with renewable integration. Variability issues that concern many are not unique to variable renewables. Grid operators have been dealing with demand variability for over a century. With sufficiently accurate forecast for variable renewables, the grid operators can schedule dispatchable generation and/or storage resources to balance demand and supply on a nearly real-time basis. With state-of-the-art wind forecasting technologies and existing generation resources, wind integration has not caused major operational problems for grid systems with a penetration level of up to 37% during some time intervals. Base load generators operate nearly constantly for days or longer and supply a larger share of the electricity mix than what is proportional to their capacity. This will be a limiting factor for high level variable renewables, if current operation continues. The capability to at least partially follow electricity load should be a key performance measure of non-renewable plants if we are serious about high level variable renewables. Specific policy instruments are recommended to incentivize more flexible plant operation and ensure smooth integration of variable renewables.